POTENSI GEOWISATA KAWASAN GUNUNG BADAK, TELUK CILETUH-SUKABUMI - -, Mega F. Rosana (Fakultas Teknik Geologi Universitas Padjadjaran, 2008)
Gunung Badak area, Ciletuh Bay, Sukabumi is area that has a rare diversity of rock at West Java region. Morphology of this area is interesting enough for one of the aspects of tourism, especially geological asptect (geotourism).This reveals the general geotourism potential in the Ciletuh Bay area. Method used in this study is a survey directly in the field and a review of some aspects of the geological literature Ciletuh. There are three groups of objects geotourism that can be developed in this area, namely: Amphiteater Morphology of Ciletuh Bay; Mandra Island; Manuk Island; Kunti Island and Lava pillows; G. Badak and G. Aseupan.Management and effective supervision are required to develop this potential to be geotourism, considering this area is part of Nature Reserve Cibanteng. Development potential to the south towards Ujung Genteng geotourism quite well developed for tourism towards the coast, and the green turtle protection.